Hypoxia inhibits growth, proliferation, and increases response to chemotherapy in retinoblastoma cells. (September 2017) - Yang, Qian; Tripathy, Arushi; Yu, Wayne; Eberhart, Charles G.; Asnaghi, Laura
Abstract: Retinoblastoma is a malignant tumor of the retina and the most frequent intraocular cancer in children. Low oxygen tension (hypoxia) is a common phenomenon in advanced retinoblastomas, but its biological effect on retinoblastoma growth is not clearly understood. Here we studied how hypoxia altered retinoblastoma gene expression and modulated growth and response to chemotherapy. The hypoxic marker lysyl oxidase (LOX) was expressed in 8 of 12 human retinoblastomas analyzed by immunohistochemistry, suggesting that a hypoxic microenvironment is present in up to two thirds of the cases. WERI Rb1 and Y79 retinoblastoma lines were exposed to 1% or 5% pO2, cobalt chloride (CoCl2 ), or to normoxia (21% pO2 ) for up to 8 days. Both 1% and 5% pO2 inhibited growth of both lines by more than 50%. Proliferation was reduced by 25–50% when retinoblastoma cells were exposed to 1% vs 21% pO2, as determined by Ki67 assay. Surprisingly, Melphalan, Carboplatin, and Etoposide produced greater reduction in growth and survival of hypoxic cells than normoxic ones. Gene expression profile analysis of both lines, exposed for 48 h to 1%, 5%, or 21% pO2, showed that glycolysis and glucose transport were the most up-regulated pathways, whereas oxidative phosphorylation was the most down-regulated pathway in hypoxia as compared to normoxia. These data support a role for hypoxia in suppressing growth, proliferation, and enhancing response of retinoblastoma cells to chemotherapy, possibly by impairing energy production through activation of glycolysis and inhibition of mitochondrial respiration. Targeting glucose metabolism or enhancing delivery of chemotherapeutic agents to hypoxic regions may improve treatment of advanced retinoblastomas. Highlights: Hypoxia inhibits growth of retinoblastoma cells. Hypoxia stabilizes HIF-1α and inhibits proliferation, without modifying invasion. Hypoxia increases the response to chemotherapy in retinoblastoma cells. Hypoxia is associated with induction of glycolysis and repression of respiration. Glycolytic inhibitors repressed growth in retinoblastoma only in hypoxic conditions.